WORKPLACE TELEPRESSURE AND WORKAHOLISM: ICT BOUNDARY CREATION AS A POTENTIAL MODERATOR - Wilder, Emily (East Carolina University, 2021)
In the current study, we investigated the relationships between workplace telepressure, workaholism, and information and communication technology (ICT) boundary creation. Workplace telepressure is the urge to stay connected and respond to work-related messages via ICTs. In addition, workaholism is the compulsive need to work incessantly. Both workplace telepressure and workaholism negatively impact employees on interpersonal, organizational, and organizational levels. Thus, we examined not just the association between workaholism and workplace telepressure, but also the potential moderating influence of ICT boundary creation. ICT boundary creation could allow employees to better divide their time at work and at home, thereby minimizing the negative consequences of workaholism and workplace telepressure. The final sample included 405 full-time staff and faculty at a large southeastern university. The results showed workplace telepressure positively related to workaholism and negatively related to ICT boundary creation. Furthermore, workaholism negatively related to ICT boundary creation. Moreover, ICT boundary creation moderated the relationship between workplace telepressure and workaholism, such that as ICT boundary creation increased, the relationship between workplace telepressure and workaholism weakened. Future research, organizational implications, and study limitations are addressed.
Keywords: workplace telepressure; telepressure; ICT boundary creation; boundaries; Psychology, Industrial; Telecommunication--Psychological aspects; Workaholism; Work-life balance